The interplay between oil and food commodity prices: has it changed over time? - Peersman, Gert; Rüth, Sebastian; Van der Veken, Wouter (CESifo working papers, 2019)
Using time-varying BVARs, we find that oil price increases caused by oil supply shocks did not affect food commodity prices before the start of the millennium, but had positive spillover effects in more recent periods. Likewise, shortfalls in global food commodity supply—resulting from bad harvests—have positive effects on crude oil prices since the early 2000s, in contrast to the preceding era.